Adult Education for Health and Wellness: A ‘State of the Field’ Feview of Emergent North American Literature - Maureen Coady (Adult Education Research Conference, 2014)
Learning about health takes place in a variety of ways over the course of one’s lifetime; adult education can play a key role in enabling individuals, communities, and societies to maintain and improve their health. This paper focuses on emergent research in adult education related to health and wellness.